The Japan-EU Economic Partnership Agreement: Economic potentials and policy perspectives - Hanns Günther Hilpert (Stiftung Wissenschaft und Politik (SWP), 2017)
At their summit on 6 July 2017, Japan and the EU reached an agreement in principle for bilateral free trade. The agreement should be ready for signing by the end of 2017. The intended liberalization of trade in goods, agriculture and services would create the world's largest free trade area – assuming the agreement is successfully concluded and ratified by parliament. Japan and Europe are sending out a strong signal against protectionism and in favour of free trade and modernizing global trade rules. While free trade in the transatlantic and trans-Pacific context may remain an illusion for some time to come, the Japan-EU Economic Partnership Agreement (JEEPA) is a realistic opportunity for trade partners at the western and eastern margins of the Eurasian continent to achieve trade-induced growth and increased prosperity. Given its prominence, JEEPA raises the following questions: What trade liberalization can be expected? Does a free trade agreement between Japan and Europe actually make sense? Who would be the winners and losers? What are the risks and limitations? What are the political implications of the European-Japanese alliance?
Keywords: 320